A Review On Automatic Detection of Brain Tumor Using Computer Aided Diagnosis System Through MRI - R, Meera; P, Dr. Anandhan (EAI Endorsed Transactions on Energy Web, 2018)
In diagnosing brain tumor using Magnetic Resonance Imaging (MRI) plays a major role in complicated stages. To extract the images, it uses a kind of nuclear magnetic resonance technique. To identify the exact region where the tumor is present is the most important task in the segmentation process. The most challenging and complicated medical image processing technique Brain image segmentation. The researchers are working towards to develop effective procedure for segmenting MRI images. In this research article Pre-processing, Enhancement and Segmentation process are deeply surveyed.
Keywords: MRI; Segmentation; CAD; Computer Tomography; Preprocessing; Enhancement